1994
DOI: 10.1001/jama.1994.03520130069035
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Mycobacterium tuberculosis Associated With Air Travel

Abstract: Data support the conclusion that M tuberculosis was transmitted from an infectious crew member to other crew members on an aircraft. Because of the clustering of TST-positive frequent flyers in October when the index patient was most infectious, transmission of M tuberculosis to passengers cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
7

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 15 publications
1
34
0
7
Order By: Relevance
“…Das Risiko des Erwerbs einer TB gilt für die meisten Urlauber als niedrig, für Langzeiturlauber in Ländern mit hoher TB-Inzidenz wird es jedoch auf 0,5-2,5% pro Jahr geschätzt [15]. Auch während langer Flugreisen besteht ein erhöhtes Infektionsrisiko bei offener TB eines Mitreisenden [16][17][18].…”
Section: Patienten Und Methodikunclassified
“…Das Risiko des Erwerbs einer TB gilt für die meisten Urlauber als niedrig, für Langzeiturlauber in Ländern mit hoher TB-Inzidenz wird es jedoch auf 0,5-2,5% pro Jahr geschätzt [15]. Auch während langer Flugreisen besteht ein erhöhtes Infektionsrisiko bei offener TB eines Mitreisenden [16][17][18].…”
Section: Patienten Und Methodikunclassified
“…Specifically, there is a higher risk of TB in people who travel (Albert and Davies 2008), and those who migrate to other countries (Menzies et al 2010). For example, some studies of people travelling by air have documented a link between people infected with TB and transmission to uninfected passengers (Driver et al 1994), but other studies have highlighted the problem of quantifying the risks of air travel (Abubakar 2010;Marienau et al 2010). However, airlines have become more aware of the risks that passengers take when travelling, and have outlined how those risks may be mitigated (Dowdall et al 2010).…”
Section: Mobility and Tbmentioning
confidence: 99%
“…In a 1994 published study, a flight attendant was found to have transmitted infection to other crew members but not clearly to any passengers [1]. Subsequently, the CDC reported on 6 (5 plus reference 1) different episodes of exposures of passengers and flight crew to TB on commercial aircraft between 1992-1995 [2].…”
Section: Tb or Not Tbmentioning
confidence: 99%